Factors Affecting Aggressive Tax Actions with Entity Size Moderated - Sabaruddin, Sabaruddin; Wahyudi, Slamet; Arimurti, Trias (Journal of Accounting Science, 2024)
General Background: Aggressive tax actions are methods used by companies to manage tax liabilities, aiming to reduce tax payments while increasing profits. Specific Background: Within the context of Indonesian coal mining companies, these actions have significant implications due to the sector's contribution to state revenues. Knowledge Gap: Despite existing studies, the role of entity size as a moderating factor in the relationship between liquidity, profitability, leverage, and tax aggressiveness remains underexplored. Aims: This study examines how liquidity, profitability, and leverage influence tax aggressiveness and assesses the moderating role of entity size. Results: The findings reveal that liquidity and leverage positively affect aggressive tax actions, while profitability has a negative effect. Entity size significantly moderates the influence of profitability and leverage but not liquidity on tax aggressiveness. Novelty: This study introduces entity size as a moderating variable, offering a new perspective on its role in aggressive tax behavior within the coal mining sector. Implications: The results highlight the importance of liquidity and leverage management in tax planning, offering insights for policymakers to curb aggressive tax strategies and for companies to align their practices with regulatory frameworks